2003
DOI: 10.1258/135763303321327984
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine screening for diabetic retinopathy: staff and patient satisfaction

Abstract: In a pilot project, telemedicine was used to conduct retinal examinations of diabetic patients in the Alta municipality of Norway. All health-care workers who were involved in the project were interviewed. The ophthalmologists found that the grading of the level of retinopathy was quicker with digital images than with slit-lamp examinations. Fifty patients with type II diabetes were invited to attend a telemedicine check-up and 42 did so. Patients were asked to complete a questionnaire after the telemedicine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 1 publication
(1 reference statement)
1
27
0
Order By: Relevance
“…In addition, the use of nonmydriatic cameras without dilating the eye and avoiding temporary vision impairment was seen as a major advantage of teleophthalmology as noted in the recent Wisconsin study [30]. PCP recommendation and stronger PCP-patient relationships were important patient motivators for using teleophthalmology, similar to other studies from Norway [21] and Wisconsin, USA [20,30]. The cost of care was the major barrier to obtaining dilated eye exams, as seen in other US based studies [16, 18-20, 31, 34-37].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In addition, the use of nonmydriatic cameras without dilating the eye and avoiding temporary vision impairment was seen as a major advantage of teleophthalmology as noted in the recent Wisconsin study [30]. PCP recommendation and stronger PCP-patient relationships were important patient motivators for using teleophthalmology, similar to other studies from Norway [21] and Wisconsin, USA [20,30]. The cost of care was the major barrier to obtaining dilated eye exams, as seen in other US based studies [16, 18-20, 31, 34-37].…”
Section: Discussionsupporting
confidence: 68%
“…We not only identified many of the same barriers to obtaining a dilated eye exam as other US based studies [18-20, 31, 32, 34, 35], but also demonstrated the value of a teleophthalmology service using nonmydriatic retinal cameras in PCP practices in overcoming such barriers. The most common stated value was convenience and the ability to overcome transportation and time management issue, as noted in other international and US studies, including a recent study of a white Caucasian rural population in Wisconsin [21,23,27,30,31,34,35]. Other value included ease of use, ability to detect disease before visual symptoms, and the knowledge provided by the photos and technicians about retinopathy and eye disease, which have been only reported thus far in international studies [21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, the competency of the practitioner on the other end and the completeness of the patient records both comprise important considerations for providers. 16 Or, trust among healthcare workers influences and directly affects attitudes toward telemedicine startup. 17 • Make sure administration does more than pay lip service.…”
Section: Whitten and Holtzmentioning
confidence: 99%
“…Nilsen [26] looks at the exchange of knowledge between the GPs and the specialists in videoconferences and how collaborative work might close knowledge gaps in daily medical practice; however, patients were not present. This is also the case for other studies [27], while it was the GP who was not involved in other studies [28,29], the exception being a study [30][31][32] where GPs had received special training to perform endoscopic otolaryngological examinations, which were conducted during a synchronous consultation with a specialist. Patient reported being satisfied with this type of consultation, and it offered the patient new ways of taking part in the consultation.…”
Section: Related Workmentioning
confidence: 94%